Comparative Study between Mathieu Repair and Snodgrass Repair in Distal Hypospadias - Ahmad Hassouna (Al-Azhar University, Faculty of Medicine (Damietta), 2020)
Background: Hypospadias is a congenital condition characterized by tissue hypoplasia of the ventral aspect of the penis, with incidence of one in 300 males [0.3%]. There is an increase incidence in those with first-degree relatives having hypospadias to about 13 times more than those without family history. Aim of the work: To compare between the meatal-based flap "Mathieu" technique and tubularized incised plate [TIP] "Snodgrass urethroplasty in treatment of distal hypospadias. Patients and Methods:This study was carried out at the Department of Surgery, Al-Azhar university hospital [Damietta], Egypt., The study consists of forty male children, suffering from distal penile hypospadias. Patients were blindly assigned into two groups;20 patients underwent Mathieu technique and another 20 patients underwent "Snodgrass urethroplasty”. Results: Both groups were comparable regarding patient age, consanguinity, maternal drug intake, urethral plate characteristics and duration of hospital study. However, Snodgrass urethroplasty is associated with significant increase of operative time [80.0±16.1 vs 60.0±9.6 minutes], significant lower complication rate [10% vs 30.0%], significantly good cosmetic appearance of the penis [100% excellent versus 40% excellent, 40% good, and 20% torsion of the shaft] and 100% slit like and vertically oriented meatus. Conclusion: Snodgrass and modified Mathieu repair are safe, and the choice of one of the techniques will depend on the surgeon's decision. Its procedure had its own advantages and disadvantages and final decision should be attributed to surgeon preferences.